Accuracy of in vivo microCT imaging in assessing the microstructural properties of the mouse tibia subchondral bone - Oliviero, S.; Millard, E.; Chen, Z.; Rayson, A.; Roberts, B.C.; Ismail, H.M.S.; Bellantuono, I.; Dall’Ara, E. (Frontiers in Endocrinology, 2023)
Osteoarthritis (OA) is one of the most common musculoskeletal diseases. OA is characterized by degeneration of the articular cartilage as well as the underlying subchondral bone. Post-traumatic osteoarthritis (PTOA) is a subset of OA caused by mechanical trauma. Mouse models, such as destabilization of the medial meniscus (DMM), are useful to study PTOA. Ex vivo micro-Computed Tomography (microCT) imaging is the predominant technique used to scan the mouse knee in OA studies. Nevertheless, in vivo microCT enables the longitudinal assessment of bone microstructure, reducing measurement variability and number of animals required. The effect of image resolution in measuring subchondral bone parameters was previously evaluated only for a limited number of parameters. The aim of this study was to evaluate the ability of in vivo microCT imaging in measuring the microstructural properties of the mouse tibia trabecular and cortical subchondral bone, with respect to ex vivo high resolution imaging, in a DMM model of PTOA. Sixteen male C57BL/6J mice received DMM surgery or sham operation at 14 weeks of age (N=8 per group). The right knee of each mouse was microCT scanned in vivo (10.4μm voxel size) and ex vivo (4.35μm voxel size) at the age of 26 weeks. Each image was aligned to a reference image using rigid registration. The subchondral cortical bone plate thickness was measured at the lateral and medial condyles. Standard morphometric parameters were measured in the subchondral trabecular bone. In vivo microCT imaging led to significant underestimation of bone volume fraction (-14%), bone surface density (-3%) and trabecular number (-16%), whereas trabecular thickness (+3%) and separation (+5%) were significantly overestimated. Nevertheless, most trabecular parameters measured in vivo were well correlated with ex vivo measurements (R2=0.69-0.81). Degree of anisotropy, structure model index and connectivity density were measured in vivo with lower accuracy. Excellent accuracy was found for cortical thickness measurements. In conclusion, in vivo microCT imaging can accurately measure cortical and trabecular morphometric parameters in the subchondral bone of the mouse tibia, making this technique suitable for studying the effect of OA and OA treatments in longitudinal mouse experiments.